Nilai-nilai hakiki upacara ritual naik dango : disusun untuk bahan ceramah yang diselenggarakan oleh Museum Negeri Kalimantan Barat - Aten, Herculanus (Museum Negeri Kalimantan Barat, 1989)
Cultural values of rites and ceremonies of Dayak ethnic group on celebrating the harvesting time; a speech.